Prototype PMSP system development for operational level in solid waste management - Faridah, Zulkipli; Zulkifli, Mohd Nopiah; Noor Ezlin, Ahmad Basri; Kie, Cheng Jack; Muhammad Afif Zafri, Khuzairi (Academic Research Publishing Group, 2018)
This paper aims to demonstrate the PMSP (Performance Measurement of Strategic Planning) System for solid waste management process. The complexity and dynamic scenarios in nature of solid waste management cause a huge implication for the management in order to thoroughly monitor the achievement of strategic planning. This condition causes the rate of generation of solid waste to increase every year. In addition, solid waste management is responsible in finding a more efficient mechanism to ensure that strategic planning plans are fully realized by the year 2020. As a result, the development of the prototype PMSP system as a user interface can help the management to analyze the progress of the strategic plan achievement more effectively. The analysis resulting from the output of the system is expected to facilitate the decision makers to assess the current level of achievement and also take the best steps holistically in line with the strategic planning of solid waste management plans. Through the development of this technology the goals of the country in social well-being and a sustainable environment could be achieved.